Avaliação do reparo de alvéolo, após exodontia, com perda de parede óssea vestibular e o uso de enxerto aloplástico - Osório, Leandro Berni (2013)
The reduction that occurs in the alveolar dimensions after tooth extraction can compromise the patients aesthetics and function. Due to the events of alveolar healing with loss of a wall were not described. The present study was designed to evaluate the characteristics of bone healing in socket with loss of a wall and test the influence of immediate treatment with alloplastic graft material. The two incisors of the sample of sixteen male rabbits, weighing between 2.5 and 3 kg, with 120 days were extracted. One of the walls was mechanically removed from its buccal aspect of the alveolar ridge 5 mm (WL) and the other was preserved (PR). Half of the sample received alloplastic graft (beta tricalcium phosphate) in both regions tested and, the remaining eight animals received no graft. Occlusive sutures were performed on all sites. The animals were grouped according to the graft presence and evaluation period as follows: Group A - no graft evaluated in two weeks, Group B - no graft and evaluated in sixteen weeks groups C and D received graft and were evaluated in two and sixteen weeks, respectively. Evaluation was performed using microtomography and histomorphology. Group A showed little material radiodense within the socket. Histological analysis showed bone tissue formation process. Group B showed more spongy bone volume with differences between WL and PR (p < 0.05). Group C exhibited distinct behavior of group A in bone formation, increasing radiodense material inside the socket and no volume difference between WL and PR. Group D showed increased bone, statistically significant when compared to group B, for both regions, with no difference between the sides. Areas had bone tissue composition, fibrous tissue, and non- resorbed particles. The wall loss negatively affect the alveolar volume. The immediate placement of alloplastic graft allowed to reduce the contraction ridge with socket wall preserved and lost, and can be an option for treatment of bone loss during the extraction. The periosteum has limitations in the containment of the particles within the graft when the absence of alveolar bone wall.